The Role of Village-Owned Enterprises (BUMDes) in Increasing Village Original Income (PADes) and Community Welfare of South Montong Baan Village, East Lombok Regency - Amalia, Rizka; Hailuddin, Hailuddin; Manan, Abdul; Harsono, Iwan (West Science Journal Economic and Entrepreneurship, 2024)
This research aims to (1) determine the role of BUMDes in increasing PADes (2) to determine the role of BUMDes in improving community welfare. The research approach used in this research is quantitative descriptive with data sources originating from primary and secondary data. Data analysis techniques (1) the role of BUMDes towards PADes using contribution analysis (2) the role of BUMDes towards community welfare using standard indicators of community welfare according to the 2005 Central Statistics Agency.The results of the research show that the role of BUMDes in improving PADes and the welfare of the South Montong Baan Village community has been quite successful in improving community welfare. 77% of the community (customers) belong to families with a high level of welfare after joining BUMDes, while the results of the contribution analysis show that the contribution BUMDes towards PADes is included in the very poor contribution criteria, namely <10%. To increase the role of BUMDes, the step that the village government must take is to be more active in providing outreach regarding BUMDes and related SHU distribution regulations that need to be updated.